Validation of a stability indicating capillary electrophoresis method for the determination of darunavir in tablets and comparison with the of infrared absorption spectroscopic method - Kogawa, Ana Carolina [UNESP]; Aguiar, Fernando Armani; Gaitani, Cristiane Masseto; Salgado, Hérida Regina Nunes [UNESP] (My University, 2014)
Darunavir (DRV) is a protease inhibitor used in the treatment of HIV infection, which constitutes a keystone in the therapy of patients infected with this virus. There is no monograph described in official compendia. The literature provides few methods of analysis for the determination of DRV in pharmaceuticals which include TLC, IR, UPLC, HPLC, HPLC-MS, HPLC-MS/MS, but there are no reports of the use of capillary electrophoresis (CE) for the determination of this drug. Thus, this research proposed the development and validation of a CE method for the determination of DRV in tablets. The method was completely validated according to the International Conference on Harmonization guidelines, showing linearity, selectivity, precision, accuracy and robustness. The migration was achieved in less than 1 minute using fused-silica uncoated capillary with an id of 50 μm and total length of 21 cm and voltage of +20 kV. The sample injection was performed in the hydrodynamic mode. The method was linear over the concentration range of 50-200 μg mL-1 with correlation coefficient 0.9998 and limits of detection and quantification of 7.29 and 22.09 μg mL-1, respectively. The drug was subjected to acid, base, oxidation and photolysis degradation. Degradation products were found interfering with the assay of DRV, therefore the method can be regarded as stability indicating. The validated method is useful and appropriate for the routine quality control of DRV in tablets.
Keywords: Capillary electrophoresis; Darunavir; Method validation; Protease inhibitor; Stability indicating; Tablets